Comparing children's explicit and implicit understanding of advertising and placement on TV. Issue 6 (2nd November 2017) - Uribe, Rodrigo; Fuentes-García, Alejandra
ABSTRACT: Although product placement is a frequently used promotional tool in local and international productions, particularly in combination with advertising, its study has been almost neglected in Latin America. This paper examines the explicit (verbal) and implicit (cued) understanding of advertising and placement in a sample of 9-, 12- and 15-year-old children from Chile. The results showed a more sophisticated comprehension of advertising in comparison with product placement. They also revealed that age is positively correlated with a more sophisticated understanding of both placement and advertising. Finally, significant differences were observed when comparing the use of verbal and cued methods. The results are discussed in terms of prior literature and their practical implications.